2016
DOI: 10.1084/jem.20160393
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF maintains controlled neutrophil mobilization during acute inflammation by negatively regulating CXCR2 signaling

Abstract: Luo et al. report that CXCR2 ligands are responsible for rapid neutrophil mobilization during early-stage acute inflammation and that G-CSF suppresses this mobilization by negatively regulating CXCR2-mediated intracellular signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 80 publications
(105 reference statements)
6
53
0
Order By: Relevance
“…4B, C and not shown). Notably, as previously reported in different models [45][46][47] , blocking G-CSF did not alter monocyte numbers in the kidney (Fig. 4D).…”
Section: Neutrophils Are Responsible For Kidney Inflammation After Sksupporting
confidence: 87%
“…4B, C and not shown). Notably, as previously reported in different models [45][46][47] , blocking G-CSF did not alter monocyte numbers in the kidney (Fig. 4D).…”
Section: Neutrophils Are Responsible For Kidney Inflammation After Sksupporting
confidence: 87%
“…IL-1 is known to be protective early during Mtb infection while exacerbating pathology during later infection, highlighting that the effects of IL-1 on adaptive immunity are complex and likely dependent on the host and infection model. G-CSF was increased in granulomas from LZD+IL-1Rn treated macaques which, combined with our observations of reduced PMN infiltrates in mouse lungs and macaque airways, indicated a paradoxical role of G-CSF as a neutrophil production and differentiation factor (30). However, in a model of LPS-induced lung injury it was shown that G-CSF blockade induced accumulation of PMNs and increased inflammation in the lungs, indicating pulmonary inflammation may not follow dogmatic rules of canonical inflammatory pathways (30).…”
Section: Discussionsupporting
confidence: 64%
“…Anti-G-CSF antibodies alone increased LPS-induced BAL neutrophil numbers and G-CSF levels, which has been reported to be due to the ability of anti-G-CSF antibodies to disinhibit CXCR2 signaling [27]. In addition, anti-G-CSF antibodies alone did not inhibit TNF or IL-6, which both contribute to the rise of BAL neutrophils [28, 29].…”
Section: Resultsmentioning
confidence: 99%